SISTEM INFORMASI AKUNTANSI KEUANGAN SEBAGAI ANALISIS RENCANA ANGGARAN BELANJA SEKOLAH DENGAN METODE BREAK EVEN POINT BERBASIS MULTI USER (STUDI KASUS: MADRASAH ALIYAH SABILUL ULUM) - Naimatul Munzaro’ah (Universitas Sains dan Teknologi Komputer, 2018)
One institution that requires an accounting information system and budget plan is an educational institution. Education funding includes all expenditures that have been budgeted through the School Income and Expense Plan (RAPBS) or School Budget Activity Plan (RKAS) to support the process of providing education in the form of services or goods. Madrasah Aliyah Sabilul Ulum has a duty to manage finances based on financial management principles so that the money in circulation can be utilized optimally. Break even point is the point where total income equals total cost or the point where profit equals zero. The computer-based accounting information system that is designed includes account data recording, student data recording, accounting transaction records, cost classifications, BEP calculations, income budgets, account data reports, general journals, financial accountability reports, expense classification reports, BEP reports, income budget reports and school budget plans.